COMPUTER TECHNOLOGIES AS INNOVATIVE MEANS OF IMPROVING THE PROFESSIONAL TRAINING OF FUTURE SPECIALISTS IN THE FINE ARTIST (Pedagogy of Higher and Secondary Education, 2009)
This article contemplate pecularitu of visual art teaching of in art graphics based department with using information technologiks.
Keywords: new information technologiks; graphics editors; computer graphics